ADOBE AFTER EFFECTS SOFTWARE VIDEO EDITING DAN MOTION GRAPHICS YANG POPULER - Pamuji, Sieska Asri (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2023)
Adobe After Effects is a popular software for video editing and motion graphics that was developed by Adobe Inc and was first released in 1993 by CoSA. After Adobe Systems acquired CoSA in 1994, Adobe After Effects became a multi-platform software and has continued to evolve over the years with more advanced features. This software is widely used in Hollywood films and by many companies in the production of promotional videos, advertisements, and other videos. Adobe After Effects is used to create special effects in videos such as animation, compositing, and color grading. It offers up to 50 different standard effects to modify and animate objects, and can even use Expressions to produce more dynamic movement. The software has several functions in the field of multimedia, including creating animations and motion graphics, adding special effects, compositing, color grading, and integration with other software. The main purpose of Adobe After Effects is to help users create high-quality videos with complex and detailed special effects. It allows users to explore their creativity by using various tools and features available in the software. Adobe After Effects is very important in video production because it can produce very complex and detailed visual effects such as explosion effects, fire effects, and special effects in Hollywood films.